Structure of three subtropical bat assemblages (Chiroptera) in the Andean rainforests of Argentina - Sanchez, Mariano Sebastian (2016)
I evaluated bat assemblages in terms of species richness, relative abundance, trophic guild structure, and seasonal changes at three sites along of the Southern Yungas forests. 845 individuals were captured, representing 25 species of three families, with an effort of 27,138 m of mist-net opened per hour. Subtropical assemblages showed a similar structure to those from tropical landmark, with a dominance of frugivorous Phyllostomid; in addition, a few species were abundant, followed by a long tail of less common species. However, subtropical sites differed due to the dominance of the genus Sturnira and the great contribution to richness of Vespertilionidae and Molossidae families. Contrarily to my original expectations, latitudinal gradient of species richness does not seem to produce significant differences in richness between the northern and southern sites, with the central site being different. Furthermore, guild structure and captures did not change between seasons. However, I found a high variation in guild structure among sites due to changes in β diversity and latitudinal lack of species with tropical filiations. These changes generated great differences in functional structure among assemblages, with eight guilds in the north and only four in the remaining sites. Moreover, other variables, such as roost site and resource availability, climatic conditions and particular attributes of each species, could also be important in determining local richness and guild structure.